2019
DOI: 10.1002/jts.22438
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Crosswalk for the PTSD Checklist: Translating DSM‐IV to DSM‐5 Using a Veteran Sample

Abstract: The fifth edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) introduced numerous revisions to the fourth edition's (DSM-IV) criteria for posttraumatic stress disorder (PTSD), posing a challenge to clinicians and researchers who wish to assess PTSD symptoms continuously over time. The aim of this study was to develop a crosswalk between the DSM-IV and DSM-5 versions of the PTSD Checklist (PCL), a widely used self-rated measure of PTSD symptom severity. Participants were 1,003 U.S. vete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
71
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 13 publications
3
71
0
1
Order By: Relevance
“…PCL-5 scores were used as the measure of PTSD symptom severity for each cluster and for overall symptom severity in all analyses including PTSD symptoms. As a result, PCL-C scores were converted to PCL-5 scores using an established and validated crosswalk procedure using equipercentile equating 61 . All interview-based assessments were conducted by trained clinical interviewers.…”
Section: Methodsmentioning
confidence: 99%
“…PCL-5 scores were used as the measure of PTSD symptom severity for each cluster and for overall symptom severity in all analyses including PTSD symptoms. As a result, PCL-C scores were converted to PCL-5 scores using an established and validated crosswalk procedure using equipercentile equating 61 . All interview-based assessments were conducted by trained clinical interviewers.…”
Section: Methodsmentioning
confidence: 99%
“…An additional exploratory GFCI analysis was performed to examine the relations among PTSD symptom clusters and depressive symptoms in the MYH sample to identify possible mechanisms of this relationship. As items of the PTSD Checklist (PCL) in MYH were formulated for the DSM-IV, we re-categorized them according to DSM-V re-experiencing, avoidance, negative alterations in cognition and mood (NACM), and hyperarousal clusters (see (67) for a previous analysis taking this approach). Multilevel confirmatory factor analysis (MLCFA) was fitted to the items, with four factors representing the DSM-V symptom clusters (see Figure S6 and the Supplementary MLCFA Method and Results).…”
Section: Resultsmentioning
confidence: 99%
“…As meaningful comparisons cannot be made between raw PCL‐C and PCL‐5 scores, an additional test‐equating procedure was used to compare the results of the present study to the results of the replicated studies. This novel test‐equating procedure, the empirical crosswalk for the PCL, was developed by Moshier and colleagues (2019) to predict equated PCL‐5 scores from observed PCL‐C scores. The applications of this crosswalk for the present and replicated studies are presented in Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to score comparisons allowed by Moshier and colleagues’ crosswalk (2019), the present and replicated studies can also be meaningfully compared by their relative effect sizes. The effect size of total PTSD symptom severity in the present study was almost equal to that found by Yarborough and colleagues (2017) and 0.3 units larger than that found by O'Haire and Rodriguez (2018; see Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation